2019
DOI: 10.1021/jacs.9b10770
|View full text |Cite
|
Sign up to set email alerts
|

An Organometallic Strategy for Assembling Atomically Precise Hybrid Nanomaterials

Abstract: For decades, chemists have strived to mimic the intricate design and diverse functions of naturally occurring systems through the bioinspired synthesis of programmable inorganic nanomaterials. The development of thiol-capped gold nanoparticles (AuNPs) has driven advancement in this area; however, although versatile and readily accessible, hybrid AuNPs are rarely atomically precise, which limits control over their surface topology and therefore the study of complex structure-function relationships. Here, we pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 60 publications
(171 reference statements)
1
55
0
Order By: Relevance
“…All four of these SGDs are able to bind to the gp120 trimer in a multivalent manner, where the different functional groups of the SGDs interact with gp120 in a correlated manner by the Coulombic and van der Waals (vdW) coupling. [ 20 ] In this multivalent coupling, different branches of SGDs can simultaneously interact with one or two gp120 monomers, as shown in Figures 4B, Figure S40, Supporting Information, for the Lactose‐SGD (15e) compound. On the other hand, the neutral GDs (non‐sulfated, 12d, 15d, 17d, and 18d) are significantly less active in their binding with gp120 (Figures S41 and S42, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All four of these SGDs are able to bind to the gp120 trimer in a multivalent manner, where the different functional groups of the SGDs interact with gp120 in a correlated manner by the Coulombic and van der Waals (vdW) coupling. [ 20 ] In this multivalent coupling, different branches of SGDs can simultaneously interact with one or two gp120 monomers, as shown in Figures 4B, Figure S40, Supporting Information, for the Lactose‐SGD (15e) compound. On the other hand, the neutral GDs (non‐sulfated, 12d, 15d, 17d, and 18d) are significantly less active in their binding with gp120 (Figures S41 and S42, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier studies of sulfonated gold NPs coupled with Human Papilloma Virus (HPV) capsids, we found that the free energy per one charged interaction (−6 kcal mol −1 ) is 12 times larger than that per one typical hydrophobic group (alkyl, −0.5 kcal mol −1 ). [ 20d ] Coulombic coupling should also dominate the binding of SGDs and gp120. Furthermore, the ranking of SGDs in order of their charged interaction contribution (Figure 4E, left) matches their binding affinities obtained from MST experiments: 15e > 17e > 12e > 18e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been extensively exploited to construct biosensors by integrating recognition units including molecular beacons, DNAzymes, and aptamers . Among these, Au−S bond‐mediated functionalization of AuNPs is the most important method . However, the Au−S bond is susceptible to harsh conditions, especially thiol compounds, leading to the non‐specific release of surface ligands or signal reporters, and high background signals for cell imaging owing to intracellular biothiols (for example, 1–10 m m glutathione (GSH)) .…”
Section: Methodsmentioning
confidence: 99%